ACCEPTANCE TESTING, COMMISSIONING AND QUALITY ASSURANCE FOR A NUCLETRON 192IR HDR BRACHYTHERAPY AFTERLOADER AT NAMS, BIR HOSPITAL - Adhikari, Kanchan P; Shah, Aarati; Achraya, Bibek; Karn, Ambuj; Chapagain, Sandhya (Scientific World, 2015)
To evaluate the accuracy of radiation dose delivered to the cancer patients by using HDR Brachytherapy and to know proposed methods for the initial source installation tests, acceptance testing and a quality assurance program are done on Nucletron MicroSelectron 192Ir HDR Brachytherapy Afterloader at NAMS, Bir Hospital. The observation of sweet spots (maximum dose distribution) by using well chamber (SI HDR 1000) and electrometer (SI CDX 2000). On the basis of the observed sweet spot, Air Kerma Strength of the source is determined. Beside this includes the conformation of step size, radioactivity of the nuclides and safety measures of the machine. A careful radiation survey has been undertaken around the brachytherapy by using well calibrated TBM-IC Mark V is a small ion chamber radiation monitor. Acceptance testing and commissioning of the HDR brachytherapy unit has been completed. Air Kerma strength in newly installed source exhibit small variation but within the limit. The step size has standard deviation 0.05 with the planned step size. The measurement of radiation level around brachytherapy shows the level is within the criteria. Nucletron MicroSelectron 192Ir HDR brachytherapy system has been implemented in our unit. The acceptance test shows that status of brachytherapy and its components are functioning well. Radiation dose which will be delivered to the cancer patients are within planned dose. Scientific World, Vol. 12, No. 12, September 2014, page 85-88